A PROSPECTIVE STUDY OF THE LONG-TERM EFFECTS OF HYPEROXEMIA DURING COPD EXACERBATION: A PROSPECTIVE COHORT STUDY. - Chhatray Marndi; Gopabandhu Patra; Bhupesh Kumar Nayak; Saubhagya Chhotaray (Student's Journal of Health Research, 2023)
Objectives This study aimed to examine the prolonged impact of hyperoxemia during acute exacerbations of chronic obstructive pulmonary disease (AECOPD), focusing on patient outcomes over 1 year. The investigation explored associations with 1-year all-cause mortality, three-month all-cause fatality, and frequent hospitalizations.  Methods This prospective cohort study carried out between March 2022 to March 2023 investigates factors associated with hyperoxemia in acute exacerbations of COPD (AECOPD) at Bhima Bhoi Medical College and Hospital in Balangir, Odisha, India. A sample of 122 AECOPD patients, categorized into hyperoxemic and nonhyperoxemic groups based on their initial ED ABG, is followed for a year post-discharge.  Results In this study involving 122 patients, baseline characteristics of hyperoxemic and nonhyperoxemic groups were largely similar, differing primarily in initial AECOPD PaO2 values. The primary outcome, assessing one-year all-cause fatality, revealed no prominent difference between hyperoxemic and nonhyperoxemic (19.0 % vs 12.8 %) cohorts. Secondary outcomes indicated higher three-month all-cause mortality in the hyperoxemic group (10.9 % vs. 4.3 %), while repeat hospitalizations within one year were comparable between groups.  Conclusion The study found no statistically significant difference in one-year all-cause mortality amongst hyperoxemic and nonhyperoxemic cohorts among 122 AECOPD patients. The results suggest that hyperoxemia may not be a major determinant of long-term mortality in AECOPD, emphasizing the need for further investigation.  Recommendation This study recommends further research to explore additional factors influencing long-term outcomes in AECOPD. Specifically, investigating the impact of hyperoxemia on short-term mortality and repeat hospitalizations may provide valuable insights for refining treatment strategies.